2023
DOI: 10.7759/cureus.33494
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Pole Sleeve Fracture of the Patella in an Adolescent: A Case Report

Abstract: An 11-year-old boy was admitted to our hospital due to severe pain in his right knee when he landed after jumping over a vaulting box. A plain X-ray image and computed tomography scan showed an avulsion fracture of the lower pole of the patella and patella alta. Furthermore, magnetic resonance imaging (MRI) revealed an articular cartilage lesion and rupture between the inferior pole of the patella and the patella tendon. We diagnosed a sleeve fracture of the patella and performed surgical treatment. Open reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Additional cerclage around the patella is recommended for comminuted fractures [14]. Other materials can be used, such as ultra-high-molecular-weight polyethylene (FiberWire), which has been shown to have better outcomes in certain types of fractures [15,16]. A recent randomized controlled trial discussed the use of headless screws in cadaver knees and showed comparable outcomes to cannulated screws for fixation strength and subfailure fragment displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Additional cerclage around the patella is recommended for comminuted fractures [14]. Other materials can be used, such as ultra-high-molecular-weight polyethylene (FiberWire), which has been shown to have better outcomes in certain types of fractures [15,16]. A recent randomized controlled trial discussed the use of headless screws in cadaver knees and showed comparable outcomes to cannulated screws for fixation strength and subfailure fragment displacement.…”
Section: Discussionmentioning
confidence: 99%